நாலடியாரில் அறம்சார் இயற்கைச் சூழலியல் / Ethical Natural Ecology in Naladiyar - பா. தினேஷ்குமார் / B. Dineshkumar (International Journal of Tamil Language and Literary Studies, 2023)
“Naladiyar” is one of the eighteen books (Pathinenkeelkanaku) that is considered didactic literature in Tamil Literature. The Jain monks composed it in the seventh century. In addition, it advises people to lead a moral life. “Naladiyar” is full of virtues and they also convey various messages related to the natural environment of the people around them, such as plants, animals, birds, and natural systems, along with the lifestyle, culture, customs, materials used, by the people of that time. The Jain sages who composed “Naladiyar” mentioned various types of morals in their books, but they did not fail to explain the living conditions of the people of that time as parables and references, such as about the flora and fauna such as animals, birds, and humans and grass, plants, vines, trees, and parts of the geography of the Tamil five lands, There are also many messages in “Naladiyar” about mountains, seas, rains and celestial bodies such as the moon, the sun, and related environments. This article presents various types of natural environments found in the forest as depicted in “Naladiyar”.